Effectiveness of Non-Cash Food Assistance Policy (BPNT) Implementation in Improving Food Security for Urban Communities in Lampung Province - Malik Malik; M Ardiansyah; Jeffrey D Straussman (LPPM Universitas PGRI Sumatera Barat, 2025)
The non-cash food assistance (BPNT) policy has been implemented in Indonesia to improve the distribution and utilization of social assistance, with the goal of strengthening household food security, increasing access to quality food, and supporting the local economic circulation. Although this policy has great potential, its implementation in urban areas, including in Lampung Province, faces significant challenges, such as limited infrastructure, gaps in digital service accessibility, logistical constraints, and low digital literacy among beneficiaries. Additionally, food price instability and a lack of distribution oversight pose obstacles to the success of this policy. This study aims to evaluate the challenges in implementing BPNT in Lampung Province and analyze its impact on food security. The results show that strengthening digital literacy, developing technological infrastructure, and cross-sector collaboration are key to improving policy effectiveness. Continuous evaluation and a holistic approach integrating social, economic, and technological factors are necessary to achieve long-term success in supporting food security for the poor in urban areas.